2018
DOI: 10.1523/jneurosci.2200-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Diminished Cortical Thickness Is Associated with Impulsive Choice in Adolescence

Abstract: Adolescence is characterized by both maturation of brain structure and increased risk of negative outcomes from behaviors associated with impulsive decision-making. One important index of impulsive choice is delay discounting (DD), which measures the tendency to prefer smaller rewards available soon over larger rewards delivered after a delay. However, it remains largely unknown how individual differences in structural brain development may be associated with impulsive choice during adolescence. Leveraging a u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 75 publications
8
52
0
Order By: Relevance
“…We recently provided evidence for a causal link between delay of gratification in intertemporal decisions and neural excitability in the right temporoparietal junction (rTPJ) [11], a brain region that is commonly associated with perspective taking in social cognition [12]. Our finding converged with other demonstrations that rTPJ activity is increased during choice of delayed reward [13,14] and that rTPJ cortical thickness relates statistically to delay of gratification [15]. Thus, the rTPJ appears to be a core node of a network that facilitates delaying gratification by enabling humans to take the perspective of their future selves.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…We recently provided evidence for a causal link between delay of gratification in intertemporal decisions and neural excitability in the right temporoparietal junction (rTPJ) [11], a brain region that is commonly associated with perspective taking in social cognition [12]. Our finding converged with other demonstrations that rTPJ activity is increased during choice of delayed reward [13,14] and that rTPJ cortical thickness relates statistically to delay of gratification [15]. Thus, the rTPJ appears to be a core node of a network that facilitates delaying gratification by enabling humans to take the perspective of their future selves.…”
Section: Introductionsupporting
confidence: 70%
“…In the intertemporal decision task, participants chose between an SS reward that was fixed to 10 Swiss francs today and an LL reward that ranged from 10 to 20 Swiss francs and that was delivered after a delay of 1 to 180 days. We fully crossed 9 reward levels (10,11,12,13,14,15,16,18, and 20 Swiss francs) with 9 different delays (1,5,10,20,40,60,90,120, and 180 days), resulting in a total of 81 reward-delay combination trials (which were presented in random order and repeated twice per session). As the amount for the SS reward option was fixed, only the amount and delay for the LL reward were presented on the screen above and below a central fixation cross, respectively.…”
Section: Task Designmentioning
confidence: 99%
“…Since impulsivity was also considered a potential factor influencing people’s risky choices (Clark et al, 2013; Studer and Clark, 2011), especially among adolescents, pathological gamblers and drug addicts (Barkley-Levenson and Galván, 2014; Chandler et al, 2009; Pehlivanova et al, 2018; Verdejo-García et al, 2008), we ran the simple regression analysis between GPT and IPT scores both in the pilot and fMRI datasets. Consistent with previous studies (Seuntjens et al, 2015), we found subjects’ GPT and IPT scores significantly correlated with each other in the pilot questionnaires ( r = 0.272, p = 0.018) as well as in the fMRI dataset ( r = 0.543, p = 0.005; Figure 2A), suggesting that IPT might be a confounding factor in identifying the specific effect of trait-greed (Supplementary file 2).…”
Section: Resultsmentioning
confidence: 99%
“…, 2013 ), vmPFC ( Bernhardt et al. , 2014 ; Pehlivanova et al. , 2018 ), lateral prefrontal cortex ( Bjork et al.…”
Section: Introductionmentioning
confidence: 99%
“…, 2013 ), insula ( Turel et al. , 2018 ) as well as temporal pole and temporoparietal junction ( Pehlivanova et al. , 2018 ).…”
Section: Introductionmentioning
confidence: 99%